a. 75: (x + 18) = 52

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

20 tháng 1 2022

\(75:\left(x+18\right)=52\)

\(\Leftrightarrow x+18=\frac{75}{52}\)

\(\Leftrightarrow x=\frac{75}{52}-18\)

\(\Leftrightarrow x=-\frac{861}{52}\)

12 tháng 1 2017

Bài 1:

a/

- (35 - x) - (y - 40) = -35 + x - y + 40

= (x - y) + [(-35) + 40) = x - y + 5

b/ 4 . (x - 3) - (2x + 18)

= (4x - 4.3) - (2x + 18)

= 4x - 12 - 2x - 18 = 4x - 2x + [(-12)+(-18)]

= 2x - 30

Bài 2:

a/ -(314 - 25) - (27 - 75) - 73

= - 314 + 25 - 27 + 75 - 73

= -314 + {(25 + 75) + [(-27) - 73]}

= -314 + (100 - 100) = -314 + 0 = -314

b/ (-56 . 77 . 90) : [-8 . 72 . (-45)]

= [-56 : (-8)] . (77 : 72) . [90 : (-45)]

= 7 . \(\frac{77}{72}\)\(\frac{77}{72}\).(-2) = -14 . \(\frac{77}{72}\) = \(\frac{-539}{36}\)

a)

x-31-17-7
2y +17-71-1
x4210-4
y3-40

-1

b)

2x +11-15-511-1155-55
3y-2-5555-1111-55-11
x0-12-35-627-28
y/19-3/-1//1

Có 4 đáp số :(x =-1; y =19)         ;     (x =2 ; y =-3)

                    (x =5 ; y =-1)          ;     (x =-28 ; y =1)

4 tháng 2 2019

a,(x-3)(2y+1)=7

Ta co: 7=1.7=7.1=(-1).(-7)=(-7).(-1)

\(\Rightarrow\)(x-3)(2y+1)=1.7 hay (x-3)(2y+1)=7.1 hay (x-3)(2y+1)=(-1).(-7) hay (x-3)(2y+1)=(-7).(-1)

TH1: \(\text{(x-3)(2y+1)=}1.7\Rightarrow\orbr{\begin{cases}\left(x-3\right)=1\\\left(2y+1\right)=7\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=3\end{cases}}\left(TM\right)}\)

TH2: \(\text{(x-3)(2y+1)=7.1}\Rightarrow\orbr{\begin{cases}\text{(x-3)=7}\\\text{ }\text{(2y+1)=1}\end{cases}\Rightarrow\orbr{\begin{cases}x=10\\y=0\end{cases}}\left(TM\right)}\)

TH3:\(\text{(x-3)(2y+1)=(-1).(-7)}\Rightarrow\orbr{\begin{cases}\text{(x-3)=-1}\\\text{(2y+1)=-7}\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=-8\end{cases}\left(TM\right)}}\)

TH4: \(\text{(x-3)(2y+1)=(-7).(-1)}\Rightarrow\orbr{\begin{cases}\text{(x-3)=-7}\\\text{(2y+1)=-1}\end{cases}\Rightarrow\orbr{\begin{cases}x=-4\\y=-1\end{cases}\left(TM\right)}}\)

                   Vay (x,y)={(4,3);(10,0);(4,-8);(-4;-1)}

b, (2x+1)(3y-2)=-55

Ta co: -55=-1.55=1.(-55)=55.(-1)=-55.1=-11.5=11.(-5)=5.(-11)=-5.11

\(\Rightarrow\)(2x+1)(3y-2)=-1.55 hay (2x+1)(3y-2)=1.(-55) hay (2x+1)(3y-2)=55.(-1) hay (2x+1)(3y-2)=-55.1 hay (2x+1)(3y-2)=-11.5

hay (2x+1)(3y-2)=11.(-5) hay (2x+1)(3y-2)=5.(-11) hay (2x+1)(3y-2)=-5.11

TH1:\(\text{(2x+1)(3y-2)=-1.55}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-1}\\\text{(3y-2)=55}\end{cases}\Rightarrow\orbr{\begin{cases}x=-1\\y=19\end{cases}\left(TM\right)}}\)

TH2:\(\text{(2x+1)(3y-2)=1.(-55)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=1}\\\text{(3y-2)=-55}\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\y=\frac{-53}{3}\end{cases}\Rightarrow}\left(loai\right)}\)

TH3:\(\text{(2x+1)(3y-2)=55.(-1)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=55}\\\text{(3y-2)=-1}\end{cases}\Rightarrow\orbr{\begin{cases}x=27\\y=\frac{1}{3}\end{cases}\left(loai\right)}}\)

TH4: \(\text{(2x+1)(3y-2)=-55.1}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-55}\\\text{(3y-2)=1}\end{cases}\Rightarrow\orbr{\begin{cases}x=-28\\y=1\end{cases}\left(TM\right)}}\)

TH5: \(\text{(2x+1)(3y-2)=-11.5}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-11}\\\text{(3y-2)=5}\end{cases}\Rightarrow\orbr{\begin{cases}x=-6\\y=\frac{7}{3}\end{cases}\left(loai\right)}}\)

TH6: \(\text{(2x+1)(3y-2)=11.(-5)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=11}\\\text{(3y-2)=-5}\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\y=-1\end{cases}\left(TM\right)}}\)

TH7:\(\text{(2x+1)(3y-2)=5.(-11)}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=5}\\\text{(3y-2)=-11}\end{cases}\Rightarrow\orbr{\begin{cases}x=4\\y=-3\end{cases}\left(TM\right)}}\)

TH8:\(\text{(2x+1)(3y-2)=-5.11}\Rightarrow\orbr{\begin{cases}\text{(2x+1)=-5}\\\text{(3y-2)=11}\end{cases}\Rightarrow\orbr{\begin{cases}x=-3\\y=\frac{13}{3}\end{cases}\left(loai\right)}}\)

6 tháng 10 2015

a, => x( 40% - 1 ) = 3,6

x( 0,4 - 1 ) = 3,6

-0,6x = -3,6

x = -3,6 : (-0,6)

x = 6 

30 tháng 4 2017

a = 6 ban nha